ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Perdagangan dan Jasa) - Togi Primayoga Pandenius Siagian; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effects of corporate governance to firm performance, which refers to study by Yasser Q.R, et al. (2011) which uses single-board system for corporate governance mechanism in Pakistan. Differently this study uses modified two-board system. Firm performance proxied by Return on Equity. This study attempts to examine it with 3 independent variables. These variables are the proportion of board of independent commissioners, the audit committee and firm size.The samples of this research are the trade and services firms that token randomly and listed in Indonesian Stock Exchange in 2009-2011. The samples are collected using random sampling method and resulted 52 firms become the samples. Hyphoteses testing using OLS (Ordinary Least Square) regression analysis.The result of this study indicates different result from previous research. Therefore, this study conclude that firm size affect firm performance significantly. But, The proportion of board of independent commissioners and audit committee don’t affect firm performance significantly. This study implicates that corporate governance mechanism should be reconstructed by system, process and structure until reach the aim of firm.